2017
DOI: 10.1016/j.matdes.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Replication of micro and nano-features on iPP by injection molding with fast cavity surface temperature evolution

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…In this work, the grating orientation was designed to be aligned with the polymer melt flow to promote filling of the cavity. It had been reported that the air in the grating cavity aligned with the flow direction could partially escape from the cavity, whereas the escape of air is limited when the grating is aligned orthogonal to the flow direction . To investigate the influence of process parameters on the replication fidelity, the range values for mold temperature ( T mold ) and holding pressure ( P holding ) were defined considering the thermal and mechanical properties of the mold insert's material and injection molding plastic material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the grating orientation was designed to be aligned with the polymer melt flow to promote filling of the cavity. It had been reported that the air in the grating cavity aligned with the flow direction could partially escape from the cavity, whereas the escape of air is limited when the grating is aligned orthogonal to the flow direction . To investigate the influence of process parameters on the replication fidelity, the range values for mold temperature ( T mold ) and holding pressure ( P holding ) were defined considering the thermal and mechanical properties of the mold insert's material and injection molding plastic material.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the influence of process parameters on the replication fidelity, the range values for mold temperature ( T mold ) and holding pressure ( P holding ) were defined considering the thermal and mechanical properties of the mold insert's material and injection molding plastic material. In the current work, the relatively low range values for mold temperature (25–40 °C) and holding pressure (100–250 bar) were used for injection molding of sub‐micron surface patterns in comparison with other works ( T mold > 100 °C and P holding > 700 bar), in which the mold inserts were made of nickel shim or silicon. For polymeric mold inserts, patterned structure on the mold underwent deformation when the mold temperature was above 50 °C (i.e., the T g of Digital ABS mold material), whereas a pronounced flash along parting lines was formed when a holding pressure above 400 bar was applied (as shown in Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The use of polycaprolactone (PCL) seems to be particularly promising, because of its biocompatibility and its capability to prolong the drug release. In the last decades, compression molding has been one of the most diffused processes for polymeric part production [20][21][22][23]. High automation, high geometrical accuracy, and the fast cycle time, which means high productivity, are the main reasons for the diffusion of this process.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical heating of the cavity surface is undoubtedly less expensive and requires small additional tool costs [ 29 , 30 , 31 , 32 , 33 ]. The electrical heating of the cavity surface was efficiently applied to the injection-molding process to obtain micro- and nanostructures surfaces of polypropylene [ 34 ].…”
Section: Introductionmentioning
confidence: 99%